Kategori Darah yang Keluar Akibat Kehamilan Anggur Perspektif Fikih Islam - Nuraeni Novira; A. Hawariah; Hijrayanti Sari; Sumayyah Binti Amir (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
The research in this thesis aims to find out the opinions of fiqh scholars about the types of blood that women are accustomed to and the category of blood that comes out due to moral pregnancy. This type of qualitative descriptive research, which refers to library research, using normative, comparative, and phenomenological approaches. The research results found are as follows; First, according to the fiqh scholars, there are three types of habituated blood, namely: 1) menstrual blood that comes out of the womb of a woman who is 9 years old or less than 16 days old when she is healthy and without cause, which comes out at a certain time; 2) puerperal blood that comes out of the uterus due to birth, after or before which is accompanied by pain; 3) istihadhah blood that comes out of the surface of the uterus in addition to the periods of menstruation and childbirth, which comes out continuously without stopping at all or stopping for a while like a day or two in a month. Second, the category of blood that comes out due to moral pregnancy is bleeding that occurs in pregnant women and is not yet in the form of a human, so the blood that comes out is istihadhah blood, fasting and prayer are obligatory even though the blood is still flowing.